If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q + -10 = 6(r + 1) Reorder the terms: -10 + q = 6(r + 1) Reorder the terms: -10 + q = 6(1 + r) -10 + q = (1 * 6 + r * 6) -10 + q = (6 + 6r) Solving -10 + q = 6 + 6r Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + q = 6 + 10 + 6r Combine like terms: -10 + 10 = 0 0 + q = 6 + 10 + 6r q = 6 + 10 + 6r Combine like terms: 6 + 10 = 16 q = 16 + 6r Simplifying q = 16 + 6r
| m+12=-5 | | x+6/4=-4x/16 | | 4x+4+5x+3=9x+7 | | 48r^2-84r+36= | | 0.25(5P-3)=0.75(3P-2) | | -6p=-3p+33 | | 2(d-1)=12(4d+3)+1 | | h(p)=p^2+2p | | x^2-25x+4x=52 | | -2u+6v=9 | | 11y+(2)3=-5y+24 | | 10y^2-7yz-6z^2= | | H/6-11=-22 | | 13(4x-3)=12 | | 12-23c=63-7c | | -2m-5n=7m-3n | | 4x^2-56x+180=58 | | 3/5x=-8 | | 2(x+4+x)=84 | | 2x+3x+2x+3=5x+11 | | 2(3x+4)=5x+1 | | a(x^2-3)-2(x^2-3)=0 | | 5+10x=2x-11 | | 5x(x+1)=5-2x | | 9x-89= | | -38-7x=2-7(x+6) | | x^3-2x^2+16x-60=0 | | 3x-8+4x+12=6x+15 | | 4x^2+8x+k=0 | | (2w+3u)(4w+3u-7)= | | 12z=21-8x | | 0.5+0.3y=0.7y-0.3. |